Development of cephalometric parameters and the proportions of the head in the population of rural children and youth aged 6–19 years from the Podkarpacie region - Nowak, Marta (European Journal of Clinical and Experimental Medicine, 2011)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction: This paper presents the development of the cephalometric characteristics and indices of the proportion of the head in children and rural youth aged 6-19 years from the Podkarpacie region in comparison with the urban set from the city of Rzeszow. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods: Anthropometric measurements were carried out in a group of 3,696 boys and girls using the Martin technique. Six metric characteristics were taken into consideration: head length (g-op), head width (eu-eu), morphological face height (n-gn), face breadth (zy-zy), nose height (n-sn) and nose width (al-al). On the basis of these parameters the following indices were calculated: cephalic, morphological facial and nasal. The data obtained were analyzed statistically using Microsoft Office Excel 2003. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results: In the rural population the morphological parameters of the head are generally lower for 6-12-yearolds or 13-year-olds, while over 13 years of age they are similar or higher compared with the urban set. Statistical significance of absolute differences in examined features was found for selected age classes. The compared populations are brachycephalic (only in 6-year-old rural boys hyperbrachycephalus was observed) and narrow-nosed. In rural boys aged 6-13 years and in urban boys aged 6-15 years euryprosopic type was observed, while in the remaining period of ontogenesis – mesoprosopic type. Rural girls aged 6-13 years are euryprosopic, while those aged 14-18 years are mesoprosopic. In the group of urban girls aged 6-14 years mesoprosopus was observed, whereas in 15-18-year-olds euryprosopus. <p class="rtejustify" style="box-sizing: border-box; margin: 0px; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusions: The issues presented in this paper should continue in the years 2014–2015 to initiate research into the phenomenon of secular trend in the population of children and youth from rural areas of Podkarpacie.